Designer Gold‐Framed Palladium Nanocubes for Plasmon‐Enhanced Electrocatalytic Oxidation of Ethanol. Issue 32 (21st April 2022) - Zhao, Yuhui; Wu, Fengxia; Wei, Jinping; Sun, Hongda; Yuan, Yali; Bao, Haibo; Li, Fenghua; Zhang, Zhichao; Han, Shuang; Niu, Wenxin
Abstract: Surface plasmon of coinage metal nanostructures has been employed as a powerful route in boosting the performances in heterogenous catalysis. Development of efficient plasmonic nanocatalysts with high catalytic performance and efficient light harvesting properties is of vital importance. Herein, we rationally designed and synthesized a plasmonic nanocatalyst composed of Au‐framed Pd nanocubes by an Ag(I)‐assisted seed‐mediated growth method. In the synthesis, the incorporation of Ag(I) suppresses the reduction of Au on the {100} surface of cubic Pd seeds and leads to the formation of Au nanoframes on the Pd nanocubes. The unique Au‐framed Pd nanocubes can integrate the superior electrocatalytic of Pd and the outstanding plasmonic properties of Au. Thus, these nanostructures were employed as plasmonic nanocatalysts for plasmon‐enhanced electrocatalytic oxidation of ethanol with improved stability. Abstract : Development of efficient plasmonic nanocatalysts with high catalytic performance and efficient light harvesting properties is of vital importance. Herein, the authors rationally designed and synthesized a plasmonic nanocatalyst composed of Au‐framed Pd nanocubes by an Ag(I)‐assisted seed‐mediated growth method. The unique Au‐framed Pd nanocubes can integrate the superior electrocatalytic of Pd and the outstanding plasmonic properties of Au. Thus, these nanostructures were employed as plasmonic nanocatalysts for plasmon‐enhanced electrocatalytic oxidation of ethanol with improved stability.